Die Großschmetterlinge (Macrolepidoptera) der Diluviallandschaften um Eberswalde - Arnold Richert (Contributions to Entomology)
The development of the macrolepidopteran fauna (butterflies and macro moths) of the diluvial landscapes around Eberswalde is updated until 2023: Changes in the number of species: Fourteen species were recorded for the first time in the area during the observation period: Pieris mannii (Pieridae), Korscheltellus lupulina (Hepialidae), Synanthedon mesiaeformis (also first record for Germany and the state of Brandenburg), Pyropteron triannuliformis (Sesiidae), Lasiocampa quercus (Lasiocampidae), Eilema caniola, Eublemma purpurina (Erebidae), Amphipyra perflua, Caradrina kadenii, Dicycla oo, Mythimna vitellina (Noctuidae), Isturgia arenacearia, Idaea rusticata, Horisme radicaria (Geometridae). Reliable first records from earlier times are now available for four further species: Pyronia tithonus (Nymphalidae, Satyrinae; historical record), Morpho helenor peleides (Nymphalidae; alien species), Euplagia quadripunctaria (Erebidae), Spodoptera exigua (Noctuidae; alien species). Ten species that had been presumed extinct in the area were rediscovered, including, as particularly noteworthy rediscoveries, the large wall brown Lasiommata maera after 66 years, and the noctuid moths Schrankia taenialis after 36 years, Hyppa rectilinea after 33 years, Apamea furva after 23 years and Hadena perplexa after 27 years. Nine species of the former species inventory are presumed extinct. Knowledge on the biology of the species, their distribution in the area and current changes in phenology is updated.